Konsep Diri Penyandang Difabel Panti Asuhan melalui Komunikasi (Studi Deskriptif Kualitatif di Lembaga Sosial Anak Panti Asuhan Stellamaris Nangahure, Kecamatan Alok Barat, Kabupaten Sikka) - Alfian Harbiyanto; Juliano Colson Lay (Departement of Mathematics Education, 2023)
The purpose of this study was to determine the process of forming the self-concept of people with disabilities through interactions between children and caregivers at the Maria Stellamaris Nangahure Orphanage and to examine appropriate communication patterns with orphanage children, especially for those with disabilities at the Maria Stellamaris Nangahure Orphanage. The communication pattern applied is the interpersonal communication pattern. The data collection method uses interviews and observations as well as documentation. The type of research carried out is qualitative research with the type of research used, namely case studies. Data analysis using Miles and Huberman techniques. The technique of checking the validity of the data using trianggulation methods. The results showed that from the findings about self-concept and communication processes, the self-concept formed in people with disabilities in orphanages varies depending on the way children and caregivers interact in daily life. The formation of the self-concept of people with disabilities in orphanages, especially those with disabilities, is greatly influenced by the people around them, especially caregivers.